2021
DOI: 10.1007/s00009-021-01781-x
|View full text |Cite
|
Sign up to set email alerts
|

On Invariant Subspaces in the Lai–Massey Scheme and a Primitivity Reduction

Abstract: In symmetric cryptography, the round functions used as building blocks for iterated block ciphers are obtained as the composition of different layers acting as a sequence of bijective transformations providing global increasing complexity. The study of the conditions on such layers which make the group generated by the round functions of a block cipher a primitive group has been addressed in the past years, both in the case of Substitution Permutation Networks and Feistel Networks, giving to block cipher desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…( 49) [42]. Also, it is shown that this algorithm defines a one-to-one function [43], which is an important property because it means that two different integers n 1 ̸ = n 2 in turn generate two different permutations.…”
Section: Algorithm For the Generation Of Permutationsmentioning
confidence: 99%
“…( 49) [42]. Also, it is shown that this algorithm defines a one-to-one function [43], which is an important property because it means that two different integers n 1 ̸ = n 2 in turn generate two different permutations.…”
Section: Algorithm For the Generation Of Permutationsmentioning
confidence: 99%
“…( 42), where T is the total number of bits in the encrypted image, and the function b(i, j) c is defined by Eq. (43).…”
Section: Parameters To Measure the Strength Of Iecc Against The Diffe...mentioning
confidence: 99%